Evaluation of B2O3 as replacement for CaF2 in CaO–Al2O3 based mould flux. (20th April 2016) - Yan, W.; Chen, W.; Yang, Y.; Lippold, C.; McLean, A.
Abstract : In order to develop low fluoride or fluoride free CaO–Al2 O3 based mould flux for casting high aluminium steel, an investigation was carried out to study the effect of substituting CaF2 with B2 O3 on heat transfer and crystallisation behaviour of CaO–Al2 O3 based mould flux by employing a heat transfer simulator of mould flux and a single hot thermocouple technique. The results showed that addition of CaF2 promoted heat transfer of CaO–Al2 O3 based mould flux, which was opposite to the effect of CaF2 on heat transfer in conventional CaO–SiO2 based mould flux. Addition of CaF2 inhibited crystallisation of CaO–Al2 O3 based mould flux by lowering the start crystallisation temperature and prolonging the incubation time of crystallisation. B2 O3 showed similar effects to CaF2 on heat transfer and crystallisation of CaO–Al2 O3 based mould flux, but its ability to promote heat transfer and suppress crystallisation was stronger than CaF2 . Ca3 B2 O6 (melting temperature 1480°C) was found as the primary crystalline phase in fluoride free CaO–Al2 O3 based mould flux compared with the primary crystalline phase Ca2 Al3 O6 F (melting temperature 1507°C) in fluoride bearing (20% CaF2 ) CaO–Al2 O3 based mould flux.